Low levels of ADAMTS‐13 with high anti‐ADAMTS‐13 antibodies during remission of immune‐mediated thrombotic thrombocytopenic purpura highly predict for disease relapse: A multi‐institutional study. Issue 8 (21st May 2020) - Schieppati, Francesca; Russo, Laura; Marchetti, Marina; Barcella, Luca; Cefis, Maurizio; Gomez‐Rosas, Patricia; Caldara, Gloria; Carpenedo, Monica; D'Adda, Mariella; Rambaldi, Alessandro; Savignano, Chiara; Billio, Atto; et al.
Abstract: Immune‐mediated thrombotic thrombocytopenic purpura (iTTP) is a life‐threatening immune‐mediated thrombotic microangiopathy. Daily therapeutic plasma exchange (TPE) and the optimized use of rituximab have strikingly improved the outcome of this disease, however the rate of disease recurrence remains high. Specific predictors of relapse in patients in remission can be relevant for an optimal patient management. In this study, we aimed to identify predictive variables of disease relapse in a multicenter cohort of 74 out of 153 iTTP patients. They were tested at different time points during remission for the levels of ADAMTS‐13 activity and autoantibody, and did not receive pre‐emptive treatment for ADAMTS‐13 activity deficiency during remission. The results showed that the association of ADAMTS13 activity ≤20% with a high anti‐ADAMTS‐13 titer at remission, and the time to response to first line treatment ≥13 days, were independent predictive factors of disease relapse. In addition, the use of rituximab in patients with exacerbation or refractoriness to TPE was significantly associated with reduced relapse rate. By Cox regression analysis, patients with ADAMTS‐13 activity ≤20% plus anti‐ADAMTS13 antibody titer ≥15 U/mL at remission had an increased risk of relapse (HR 1.98, CI 95% 1.087‐3.614; P < .02). These findings may help to outline more personalized therapeutic strategies in order to provide faster and sustained responses to first‐line iTTP treatment and prevent relapses in these patients.